Inflammatory rheumatic diseases and the risk of Parkinson's disease: A systematic review and meta-analysis - He, Lili; Zhao, Hecong; Wang, Fuli; Guo, Xiaoyan (Frontiers in Neurology, 2022)
Background Several studies showed inconsistencies in the relationships between inflammatory rheumatic diseases (IRDs) and the risk of Parkinson's disease (PD). Therefore, we carried out a meta-analysis to investigate the associations between different IRDs and PD risk. Methods A comprehensive search was undertaken on PubMed, Embase, Cochrane Library, and Web of Science databases up to June 2022. Studies reporting the relationships between IRDs and PD risk were included. Pooled relative risks (RRs) with 95% confidence intervals (CIs) were calculated by using random-effects models. Results Twenty-two publications covering seven IRDs containing data from 833,004 patients were identified for quantitative analysis. The pooled results indicated that ankylosing spondylitis (RR = 1.55, 95% CI: 1.31–1.83, I2 = 32.1%, P < 0.001), Sjögren's syndrome (RR = 1.34, 95% CI: 1.22–1.47, I2 = 58.5%, P < 0.001), and Behcet's disease (RR = 1.93, 95% CI: 1.07–3.49, I2 = 57.6%, P = 0.030) were associated with an increased PD risk. However, no significant associations were observed between gout, rheumatoid arthritis, systemic lupus erythematosus, as well as polymyalgia rheumatica and the subsequent development of PD. Conclusion Ankylosing spondylitis, Sjögren's syndrome, and Behcet's disease may increase PD risk.